The effects of counterfactual thinking on everyday meaning - TAN, Wynn (Institutional Knowledge at Singapore Management University, 2022)
Meaning-making literature largely focuses on predictors of global meaning rather than situational meaning. This is insufficient as both levels of meaning are necessary for a sustained sense of meaning. Past studies found evidence that downward counterfactuals can enhance the meaningfulness of events. However, those findings may be due to existing studies’ focus on major events and did not study how meaning could change over time. For everyday events, upward counterfactuals were proposed to be more apt in enhancing meaning. Using a multiphase diary study, this paper examined whether upward counterfactual thinking predicted event meaningfulness, and more specifically if it was through learning lessons from those events. Event valence (i.e., positive vs negative) and individuals’ implicit theories (i.e., growth vs fixed mindset) were explored as factors that could moderate this relationship. Interestingly, rather than enhancing meaning, upward counterfactuals reduced the meaning of positive events and preserved the meaning of negative events over time. In addition, there was support for a moderated mediation model: lesson learning mediated the relationship between upward counterfactuals and event meaningfulness—but this mediation pathway applied to negative events only. Individuals’ growth theory did not moderate the effects. Limitations, theoretical, and practical implications of the study were discussed.